2021
DOI: 10.11648/j.ijsspe.20210604.11
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Gender, Age and Competitive Level on Elite Student-athletes’ Religious Coping Experiences in the Week Leading Up to Competition

Abstract: In recent times, religiosity and spirituality have been embraced by most athletes as alternative coping mechanism around the world. Although extensive scholarly works on different dimensions of coping exist in sport, only few studies have explored the use of other coping strategies like religious coping. The current study investigated elite student-athletes' religious coping strategies as a function of gender, age and competitive level in the week leading up to competition. This cross-sectional study convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Empirical studies have demonstrated that many people rely on religiousness as an internal resource to understand, cope and deal with adverse life events or stressful situations (e.g., Pargament, 2012 ; Abu-Raiya et al, 2015 ; Abu-Raiya and Pargament, 2015 ; Vishkin and Tamir, 2020 ). For example, persons with professed spiritual backing (e.g., faith in God and use of prayer as coping resources) were more likely to manage better with high levels of life-event stress (e.g., Hagan and Schack, 2017 ; Hagan et al, 2019 ; Frimpong et al, 2021 ; Hagan, 2021 ; Vishkin, 2021 ). One mechanism through which religion exerts its positive effects on people during times of stress is religious coping [RC] ( Ano and Vasconcelles, 2005 ; Cummings and Pargament, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Empirical studies have demonstrated that many people rely on religiousness as an internal resource to understand, cope and deal with adverse life events or stressful situations (e.g., Pargament, 2012 ; Abu-Raiya et al, 2015 ; Abu-Raiya and Pargament, 2015 ; Vishkin and Tamir, 2020 ). For example, persons with professed spiritual backing (e.g., faith in God and use of prayer as coping resources) were more likely to manage better with high levels of life-event stress (e.g., Hagan and Schack, 2017 ; Hagan et al, 2019 ; Frimpong et al, 2021 ; Hagan, 2021 ; Vishkin, 2021 ). One mechanism through which religion exerts its positive effects on people during times of stress is religious coping [RC] ( Ano and Vasconcelles, 2005 ; Cummings and Pargament, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this decision is not to refute the findings of studies which adopted the RCOPE scale responses as continuous but to expand on the utility of the Brief RCOPE instrument using a different approach and thus, contributing to the validity evidence of the measure. In Sub-Sahara Africa, research on religion and spirituality among different samples has increased in recent years, with some studies in Nigeria (e.g., Amadi et al, 2016a ), Uganda ( Mutumba et al, 2017 ), and Ghana ( Frimpong et al, 2021 ; Hagan, 2021 ). Although these authors employed the Brief RCOPE in their studies, information on the psychometric properties and performance of the scale across the chosen samples were not reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations